Clinical, Pathological, and Genetic Characteristics in Patients with Focal Segmental Glomerulosclerosis. Issue 8 (25th August 2022) - Nagano, China; Hara, Shigeo; Yoshikawa, Norishige; Takeda, Asami; Gotoh, Yoshimitsu; Hamada, Riku; Matsuoka, Kentaro; Yamamoto, Masaki; Fujinaga, Shuichiro; Sakuraya, Koji; Kamei, Koichi; Hamasaki, Yuko; et al.
Key Points: We investigated the association between focal segmental glomerulosclerosis histologic variants (Columbia classification) and monogenic variant detection rates. The perihilar variants had the strongest association with detection of monogenic variants. The tip variants had the weakest association with detection of monogenic variants. Visual Abstract: Abstract : Background: Approximately 30% of children with steroid-resistant nephrotic syndrome (SRNS) have causative monogenic variants. SRNS represents glomerular disease resulting from various etiologies, which lead to similar patterns of glomerular damage. Patients with SRNS mainly exhibit focal segmental glomerulosclerosis (FSGS). There is limited information regarding associations between histologic variants of FSGS (diagnosed using on the Columbia classification) and monogenic variant detection rates or clinical characteristics. Here, we report FSGS characteristics in a large population of affected patients. Methods: This retrospective study included 119 patients with FSGS, diagnosed using the Columbia classification; all had been referred to our hospital for genetic testing from 2016 to 2021. We conducted comprehensive gene screening of all patients using a targeted next-generation sequencing panel that included 62 podocyte-related genes. Data regarding patients' clinical characteristics and pathologic findings were obtained from referring clinicians. We analyzed the associations of histologic variants with clinical characteristics, kidney survival, and gene variant detection rates. Results: The distribution of histologic variants according to the Columbia classification was 45% ( n =53) FSGS not otherwise specified, 21% ( n =25) cellular, 15% ( n =18) perihilar, 13% ( n =16) collapsing, and 6% ( n =7) tip. The median age at end stage kidney disease onset was 37 years; there were no differences in onset age among variants. We detected monogenic disease-causing variants involving 12 of the screened podocyte-related genes in 34% (40 of 119) of patients. The most common genes were WT1 (23%), INF2 (20%), TRPC6 (20%), and ACTN4 (10%). The perihilar and tip variants had the strongest and weakest associations with detection of monogenic variants (83% and 0%, respectively; P <0.001). Conclusions: We revealed the distributions of histologic variants of genetic FSGS and nongenetic FSGS in a large patient population. Detailed data concerning gene variants and pathologic findings are important for understanding the etiology of FSGS.